HUBUNGAN PENGETAHUAN DENGAN SIKAP DAN HIGIENE PERORANGAN (PERSONAL HYGIENE) PENJAMAH MAKANAN PADA PENYELENGGARAAN MAKANAN ASRAMA PUTRI - Edinda Ayu Miranti; Annis Catur Adi (Universitas Airlangga, 2016)
Food service provider of student dormitory have to pay attention to the principles of hygiene and sanitation. One of factors that support the principles of hygiene and sanitation on f ood service establishment is p ersonal hygiene of food handlers, in order to prevent contamination of food. Knowledge and a ttitude of food handlers can affect the p ersonal hygiene behavior of food handlers. The purpose of this study was to analyze correlation of k nowledge with a ttitude and p ersonal hygiene of food handlers in f ood service provider of female student dormitory. This study was an observational study with cross sectional design. The sample of this study was all food handlers at f ood service provider of female student dormitory Al Izzah Batu City and Ar Rohmah and it was twenty respondents with saturated sampling method (population < 30). The analysis technique used in this study was Spearman’s Rank test. The results showed that most food handlers have good knowledge (55.0%) and attitude (65.0%), meanwhile personal hygiene were moderate (85.0%). The test results showed that there was no correlation between knowledge and attitude (p>0.10), but there was a correlation between knowledge and personal hygiene (p>0.10). This study concluded that knowledge is not the only factor that can inﬂ uence the attitude, but knowledge is one of factors that may affect personal hygiene of food handlers. Food organizer of female student dormitory needs to improve the supervision and give hygiene and sanitation training for food handlers.